Development and validation of a hydrophilic interaction ultra‐high‐performance liquid chromatography with triple quadrupole MS/MS for the absolute and relative quantification of amino acids in Sophora alopecuroides L.†. Issue 14 (18th June 2013) - Wang, Hanqing; Duan, Jin‐ao; Guo, Sheng; Qian, Dawei; Shang, Erxin
<x xml:space="preserve">Abstract</x> Amino acids are naturally occurring compounds in many edible or medicinal plants, which possess a variety of pharmacological effects on humans. The aim of this study is to develop and validate a hydrophilic interaction LC coupled with MS/MS method for the absolute and relative quantification of amino acids without derivatization. The application of this method has been proven through 20 naturally occurring amino acids in 21 samples from different parts and phenological growth stage of Sophora alopecuroides. The method was performed on an ultra‐high performance LC separation system coupled with ESI‐MS on a triple quadrupole mass spectrometer. The proposed absolute quantitative method was fully validated in terms of linearity, sensitivity, precision, repeatability as well as recovery. The analysis results showed that S. alopecuroides is rich in free amino acids. In addition, relative quantitative determination of amino acids with several amino acids selected for the best accuracy was investigated. The accuracies of relative quantitative method for amino acids determinations suggest that it is feasible to quantify amino acids by the proposed relative quantitative determination method, which contributes to breaking through the choke point of lack of standards.